2022
DOI: 10.3390/en15249370
|View full text |Cite
|
Sign up to set email alerts
|

Refurbishment of Natural Gas Pipelines towards 100% Hydrogen—A Thermodynamic-Based Analysis

Abstract: Hydrogen is a key enabler of a sustainable society. Refurbishment of the existing natural gas infrastructure for up to 100% H2 is considered one of the most energy- and resource-efficient energy transportation methods. The question remains whether the transportation of 100% H2 with reasonable adaptions of the infrastructure and comparable energy amounts to natural gas is possible. The well-known critical components for refurbishment, such as increased compressor power, reduced linepack as well as pipeline tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…While over 45,000 hp compressors are needed for the 80:20% methane-hydrogen blend, the compressor hp needed for pure hydrogen is slightly below that because pure hydrogen offers less resistance to flow (frictional and viscous drags) than blends of hydrogen and methane owing to its low density and high compressibility combination. This is consistent with the estimate of the number of compressor stations required for the pipeline transportation of varying blends of methane and hydrogen over 6000km results of similar investigations by Klopcic et al in 2022 [18].…”
Section: Estimating Compressors Horsepower For Pipeline Expansion Via...supporting
confidence: 92%
See 1 more Smart Citation
“…While over 45,000 hp compressors are needed for the 80:20% methane-hydrogen blend, the compressor hp needed for pure hydrogen is slightly below that because pure hydrogen offers less resistance to flow (frictional and viscous drags) than blends of hydrogen and methane owing to its low density and high compressibility combination. This is consistent with the estimate of the number of compressor stations required for the pipeline transportation of varying blends of methane and hydrogen over 6000km results of similar investigations by Klopcic et al in 2022 [18].…”
Section: Estimating Compressors Horsepower For Pipeline Expansion Via...supporting
confidence: 92%
“…The study emphasizes the need for off-grid storage options due to the reduced line pack with hydrogen. Further research is suggested to analyse hydrogen quality during transport and assess the compatibility of pipeline components with hydrogen [18]. As a complement to their work, this study will also quantify the extent to which hydrogen presence in natural gas streams increases the logistical expenses (specifically, compressors and reinforcement pipeline materials) when an expansion of the gas pipeline is desired for it to be repurposed for hydrogen transportation, using the ELPS shown in Figure 4 as the case study.…”
Section: Introduction To Pipeline Expansionmentioning
confidence: 99%
“…[ 36 ] Recompression becomes necessary when the pressure drops to ≈50% of its initial value, which in this case is around 30–35 bar. [ 37 ] Based on the distance at which recompression is necessary, the number of compressor stations is calculated. Figure 1 and 2 show the pressure drop over distance with different mass flow rates for pipeline with 100 and 200 mm diameter, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The enthalpy of adsorption for hydrogen to these materials is very high, which shows a strong interaction between hydrogen and metals. [52][53][54] However, these materials have faced many challenges, such as materials synthesis, system cost, durability/operability, charging/discharging rate, system life-cycle, and lack of understanding of hydrogen adsorption/desorption kinetics to use hydrogen energy storage technologies in mobile transportation and power station applications. Fig.…”
Section: Tripti Rimzamentioning
confidence: 99%